The influence of learning technology on the formation of research skills in primary school students: Action research - Yespolova, Gulden; Irodakhon, Kholdarova; Bekzod, Baydjanov; Rabiga, Bazarbekova; Zhupat, Astambayeva (Journal of Education and e-Learning Research, 2023)
This study aims to determine the effectiveness of the author's teaching technology in developing schoolchildren's research skills, the challenges an elementary school faces, and how the entire process of developing research skills works. Quantitative and qualitative research techniques were used. Participants were from No.15, No.1, No.46, and No.16 schools in Ust-Kamenogorsk (East Kazakhstan). A random selection was made of an EG comprising 176 students and a CG comprising 173 students. To test the hypothesis that the author's teaching technology in studying natural science fosters the effectiveness of generating research skills, the research methodology employed an experimental pretest-posttest learning CG and EG study. As a result of the introduction of the developed technology in the EG, the levels of formation of these skills among students from the CG and the EG differ significantly. Finally, the developed technology can be used in the practical activities of teachers in elementary schools and serve as the basis for creating methodological materials that perform the developing function of teaching "Natural Science."